The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3766/jaaa.16111
|View full text |Cite
|
Sign up to set email alerts
|

Mild-Gain Hearing Aids as a Treatment for Adults with Self-Reported Hearing Difficulties

Abstract: The results from the present study suggest that adults who present with complaints of HD even in the presence of normal hearing sensitivity represent a unique population that warrants further evaluation beyond the standard hearing test. Furthermore, results from the hearing aid trial suggest that mild-gain amplification is a viable treatment option for at least some individuals with HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 63 publications
2
30
1
Order By: Relevance
“…Individual studies and several literature reviews have repeatedly identified perceived hearing difficulties as the key factor for hearing aid uptake and use (e.g., Knudsen et al 2010 ; Laplante-Levesque et al 2012 ; Hickson et al 2014; Pronk et al 2017 ; Ratanjee-Vanmali et al 2019 ; Sawyer et al 2019 ; Simpson et al 2019 ). Many older adults with slight amounts of pure-tone hearing loss, well within the WHO-new HI range of “normal” hearing, seek hearing aids and obtain positive outcomes ( Roup et al 2018 ; Humes 2020a ; Singh & Doherty 2020 ). These individuals are already well motivated as they have perceived hearing needs that compromise their auditory wellness.…”
Section: Possible Implementation and Applicationmentioning
confidence: 99%
“…Individual studies and several literature reviews have repeatedly identified perceived hearing difficulties as the key factor for hearing aid uptake and use (e.g., Knudsen et al 2010 ; Laplante-Levesque et al 2012 ; Hickson et al 2014; Pronk et al 2017 ; Ratanjee-Vanmali et al 2019 ; Sawyer et al 2019 ; Simpson et al 2019 ). Many older adults with slight amounts of pure-tone hearing loss, well within the WHO-new HI range of “normal” hearing, seek hearing aids and obtain positive outcomes ( Roup et al 2018 ; Humes 2020a ; Singh & Doherty 2020 ). These individuals are already well motivated as they have perceived hearing needs that compromise their auditory wellness.…”
Section: Possible Implementation and Applicationmentioning
confidence: 99%
“…They reported that statistically significant improvements were obtained with MSAT, which improved SIN scores and SNRs (6.3 dB on average). 22 described results for 20 normal-hearing adults (19-27 years of age) with no self-reported HDs and 19 normal-hearing adults (18-58 years of age) with self-reported HDs. All were fitted binaurally with mild-gain, receiver-in-the-canal (RIC) hearing aids for a four-week trial with directional and noise reduction algorithms engaged.…”
Section: Hearing Aids Can Improve Hds and Sin Problemsmentioning
confidence: 99%
“…Roup, Post, and Lewis 9 note mild gain hearing aids (with noise reduction and directional microphones) are a viable option for people with normal hearing and subjective hearing difficulties. 9 Post, Roup, and Lewis 10 reported an increasing body of evidence demonstrating that adults with normal hearing sensitivity may report substantial difficulty understanding speech in complex listening situations. They report some hearing care professionals have fitted personal mild-gain amplification as an option to help these adults.…”
Section: Improving the Snr In The Presence Of Normal Peripheral Hearingmentioning
confidence: 99%